Coiled-Coil Domain-Containing Protein 45 Is a Potential Prognostic Biomarker and Is Associated with Immune Cell Enrichment of Hepatocellular Carcinoma - Liu, Shuqing; Jia, Lei; Quan, Bing; Rong, Guang; Li, Min; Xie, Ronggen; Cai, Yanling; Bi, Yuzhen; Han, Siyuan (Disease Markers, 2022)
Objective. The role of coiled-coil domain-containing protein 45 (CCDC45) in the development of hepatocellular carcinoma (HCC) has not been reported. The present study is aimed at investigating the expression and prognosis of CCDC45 in HCC and its relevance to immune infiltration. Methods. We conducted CCDC45 expression analysis using The Cancer Genome Atlas (TCGA) tumor database, the Human Protein Atlas (HPA) database, and the Tumor Immunological Evaluation Resource (TIMER). We used the University of Alabama at Birmingham Cancer data analysis Portal (UALCAN) database to show the correlation of CCDC45 with clinical features. We examined the prognostic impact of CCDC45 expression levels on HCC patients with the Kaplan-Meier mapper database. Genes coexpressed with CCDC45 and its regulators were also identified using LinkedOmics. The enriched Gene Ontology (GO) categories and associated signaling pathways were estimated using GO, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Set Enrichment Assay (GSEA) pathway data. Correlations between CCDC45 and cancer immune infiltration was analyzed through the TIMER and an integrated repository portal for Tumor-Immune System Interactions (TISIDB) databases. Results. The expression of CCDC45 was elevated in HCC tissues compared to adjacent liver tissues, and overexpression of CCDC45 was significantly correlated with tumor stage. Furthermore, HCC patients with CCDC45 overexpression had a shorter overall survival (OS). Functional network analysis indicated that CCDC45 was involved in homologous recombination, spliceosome, and DNA replication. Interestingly, CCDC45 expression was positively correlated with the level of immune cell infiltration. Conclusions. CCDC45 is associated with prognosis and immune infiltration of HCC and may be a potential therapeutic target for HCC.